HALAL CERTIFICATION STRATEGY IN THE DEVELOPMENT OF SMALL AND MEDIUM INDUSTRIES - Mahri, A. Jajang W.; Gelda, Isnaeni; Juliana, Juliana; Cahkyaneu, Aneu; Selamet Rusydiana , Aam (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: This research was carried out to find out appropriate alternative strategies from halal certification institutions in their contribution to developing Small and Medium Industries (SMI).   Method: The method uses quantitative descriptive methods; this research analyzes strategies based on expert judgment surveys. In the process, the collected data is analyzed internally and externally and developed in a matrix using SWOT analysis. Meanwhile, quantitative tools use the IFAS-EFAS approach in the form of rating and weighting questionnaires.     Result: Based on the results of the SWOT analysis, the halal certification strategy can be optimized through a combination of SO, WO, ST, and WT strategies. Based on the results of the IFAS EFAS assessment, the halal certification strategy occupies quadrant I, namely growth and build. Explains conditions that are in the growth stage and must be developed. This research shows the position of halal certification institutions in the IA quadrant with the "Rapid Growth" strategy, where the S>O value supports the SO strategy.   Conclusion and Suggestion: This research succeeded in uncovering strengths, weaknesses, opportunities, and threats and produced appropriate alternative strategies to be implemented by halal certification institutions in developing SMI. Based on the results of the IFAS EFAS alternative strategy analysis, halal certification institutions need to increase cooperation with external parties, collaborating with the government and training institutions. From the internal side, strengthening institutional operational systems, education, and communication, as well as disseminating information, must be distributed evenly to the community so that the implementation of strategies runs well.